1981
DOI: 10.1111/j.1151-2916.1981.tb15896.x
|View full text |Cite
|
Sign up to set email alerts
|

Strength Distributions of SiC Ceramics After Oxidation and Oxidation Under Load

Abstract: The room-temperature strength distributims of a sintered and a hot-pressed S i c were examined as-machined, after oxidation at 1370"C, and after oxidation under load at 1370°C. The strengths were observed to be dependent on both the duration of oxidation and the magnitude of the applied load. Processes resulting in both strengthening and weakening behavior were observed to occur, at times simultaneously within the same strength distribution. This dynamic situation indicates that the strength-controlling flaw p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…Whenever the oxide layer became thicker, the crack blunting effect was negated by the generation of new defects, either within the oxide scale or at the interface between the substrate and the oxide scale. [22][23][24][25][26][27] Thus, when the oxidation temperature was 1400°and 1500°C, the strength retention decreased slightly (2.5% and 15%, respectively) as a result of the formation of thick oxide layers.…”
Section: August 1998 Oxidation and Strength Retention Of Si 3 N 4 Andmentioning
confidence: 99%
“…Whenever the oxide layer became thicker, the crack blunting effect was negated by the generation of new defects, either within the oxide scale or at the interface between the substrate and the oxide scale. [22][23][24][25][26][27] Thus, when the oxidation temperature was 1400°and 1500°C, the strength retention decreased slightly (2.5% and 15%, respectively) as a result of the formation of thick oxide layers.…”
Section: August 1998 Oxidation and Strength Retention Of Si 3 N 4 Andmentioning
confidence: 99%
“…Passive oxidation could, in fact, have a beneficial effect by healing surface cracks and increasing the average flexural strength, while active oxidation could lead to new surface flaws that would decrease the average flexural strength [39]. The roles of material processing and composition were found to be important factors for both the distribution of strength [40], Tables 6 and 7, and the retention of strength, Fig. 5, under long-term exposures to oxidizing environments [41].…”
Section: Sicmentioning
confidence: 99%
“…Recent work has shown that ~100 nm SiO 2 glass scales increase SiC fiber strength for near‐stoichiometric SiC fibers such as Hi‐Nicalon™‐S, but thicker, crystallized scales degrade strength. Ambiguous effects of oxidation on SiC strength have been observed for bulk material …”
Section: Introductionmentioning
confidence: 98%
“…Ambiguous effects of oxidation on SiC strength have been observed for bulk material. 57,58 Single filament tensile strengths are measured for Hi-Nicalon TM -S SiC fiber after oxidation for up to 100 hours in dry and wet air at 700°C-1400°C. Preliminary results were presented elsewhere.…”
Section: Introductionmentioning
confidence: 99%